Morphology characterisation of inclusions to predict the breakdown strength in electro-ceramic materials: Microstructure modelling. Issue 1 (January 2019) - Naderi, Sadjad; Heath, James P.; Dean, Julian S.
Abstract: Microstructural features such as pores, secondary phases and inclusions can significantly alter the electrical response of ceramics. Here we present a morphological finite element approach to better understand the effect of such microstructural defects on the behaviour of electroceramics. We generate irregular three-dimensional geometric models with realistic features and controllable parameters providing a method of characterising their morphology using sphericity, signifying irregularity, and projected area. The inclusion models are solved for their electrical response for changes in the material properties, making the feature either insulating or conductive in relation to the surrounding material. The electric field distribution analysis indicates the irregularity has a significant effect on the electric response, increasing the field concentration up to 12 times more than the applied field. Plotting the electric field distribution using a Weibull cumulative Probability Distribution Function we have also estimated the breakdown strength of the material. This shows that a material's breakdown strength can be reduced to 55% for an 87.5% dense sample if the inclusion is insulative and has a low sphericity or high projected area. This can be further reduced to only 40% if the feature is more conductive than the ceramic. Graphical abstract: Highlights: Irregular structure of inclusion is essential to be implemented in FE model. Single irregular intra-grain inclusion can enhance electrostatic field concentration up to 12 times more than applied field. Breakdown strength can be degraded down to 40% of a fully dense material. Conductive inclusions promote high electric fields into the surround material.